OPTIMASI DISTRIBUSI AIR MINUM PDAM MENGGUNAKAN PENDEKATAN FUZZY INTEGER TRANSPORTATION PROBLEM - Imam Suprayogi (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2011)
The objective of this research was to develop an optimum model of water supply company distribution in Jogyakarta. Optimation was conducted to meet the need of water supply distribution from reservoirs to the service areas, so that the economical cost could be identified. This research used fuzzy integer transportation problem (FITP) model in the optimation process of water supply company distribution from Gemawang, Gedong Kuning, and Tegalrejo reservoir to service areas in North, South, East, and West Jogyakarta. This approach used transport models with Lingo program package version 8.0. Secondary data from Water Supply Company of Jogyakarta, which comprised reservoir capacity, amount of clean water needs of service area, and operating costs in each service area, were used. The results showed that the optimum water supply distribution cost was Rp. 1.591.320,00. The optimum distributions of water supply were 15.000 L from the Gemawang’s reservoir, 19.500 L from Gedong Kuning’s reservoir, and 17.500 L from Tegalrejo reservoir. Therefore, the cost was Rp.1.591.320, which was cheaper than the current cost of the Water Supply Company of Jogyakarta, which was Rp.1.600.000,00.